Casting powder and casting method

JP2025033390AActive Publication Date: 2025-03-13YAMATO STEEL CO LTD
View PDF 13 Cites 0 Cited by

Patent Information

Application Number
JP2023139088
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2023-08-29
Publication Date
2025-03-13
Estimated Expiration
2043-08-29

AI Technical Summary

Benefits of technology

【0009】 本発明によれば、熱間脆化を抑制することができる鋳造用パウダーおよび鋳造方法を提供することができる。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025033390000001_ABST
    Figure 2025033390000001_ABST
Patent Text Reader

Abstract

To provide a casting powder and a casting method capable of suppressing hot embrittlement.SOLUTION: A casting powder comprises silicon oxide, aluminum oxide, calcium oxide, and nickel oxide, wherein the content of sodium oxide is less than 3 mass% and the content of fluorine is less than 5 mass%.SELECTED DRAWING: Figure 5
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a casting powder and a casting method. [Background technology]

[0002] If copper is contained in a slab cast from molten steel in a casting process, the slab may suffer from hot embrittlement. Therefore, a technique has been disclosed for suppressing hot embrittlement by scattering a casting powder containing NiO into molten steel (see, for example, Patent Document 1). [Prior art documents] [Patent documents]

[0003] [Patent Document 1] Special Publication No. 2018-520004 Summary of the Invention [Problem to be solved by the invention]

[0004] However, if the viscosity of the casting powder to be scattered on the molten steel is low, the reduction reaction of nickel oxide may not be sufficiently promoted.

[0005] The present invention has been made in consideration of the above-mentioned problems, and has an object to provide a casting powder and a casting method capable of suppressing hot embrittlement. [Means for solving the problem]

[0006] The casting powder according to the present invention is characterized in that it contains silicon oxide, aluminum oxide, calcium oxide, and nickel oxide, has a sodium oxide content of less than 3 mass%, and has a fluorine content of less than 5 mass%.

[0007] The nickel oxide content may be 20.0 mass% or less. The silicon oxide content may be 27.1 mass% or more and 42.0 mass% or less. The aluminum oxide content may be 2.9 mass% or more and 7.5 mass% or less. The calcium oxide content may be 20.1 mass% or more and 39.0 mass% or less. The magnesium oxide content may be 0.0 mass% or more and 1.9 mass% or less. The lithium oxide content may be 2.2 mass% or less. The sodium oxide content may be 1.1 mass% or less. The fluorine content may be 2.6 mass% or less. The boron oxide content may be 2.9 mass% or less. The calcium oxide / silicon oxide content ratio may be 1.2 or less. The carbon content may be 13.8 mass% or less.

[0008] The casting method according to the present invention is characterized by comprising the steps of pouring molten steel having a Ni / Cu ratio of less than 0.9 into a mold and scattering the casting powder on a surface of the molten steel, and semi-solidifying the molten steel in the mold to obtain a cast piece. Effect of the Invention

[0009] According to the present invention, it is possible to provide a casting powder and a casting method capable of suppressing hot embrittlement. [Brief description of the drawings]

[0010] [Figure 1] FIG. 1 illustrates a process for producing shaped steel from scrap iron. [Diagram 2] FIG. 2 is a diagram for explaining hot embrittlement. [Diagram 3] FIG. 1 illustrates a state diagram. [Figure 4] FIG. [Diagram 5] FIG. 2 is a diagram illustrating a mechanism for suppressing hot embrittlement when a casting powder according to an embodiment is used. [Figure 6]FIG. 2 is a diagram showing the relationship between the Ni / Cu ratio and the Cu alloy liquid phase. [Figure 7] FIG. 1 is a diagram showing the results of Reference Example 1. [Figure 8] FIG. 13 is a diagram showing the results of Reference Example 2. [Figure 9] 1(a) and (b) are diagrams illustrating the experimental setup. [Figure 10] FIG. 1 illustrates an experimental procedure. [Figure 11] FIG. 1 shows the results of Example 1. [Figure 12] FIG. 13 is a diagram showing the results of Comparative Example 2. [Figure 13] (a) and (b) show the results. [Figure 14] FIG. 1 shows the results of Example 11. [Figure 15] FIG. 1 shows the results of Example 12. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0011] FIG. 1 is a diagram illustrating a process for producing steel of a predetermined shape from scrap iron. As illustrated in FIG. 1, scrap iron is melted in an electric furnace, then undergoes a secondary refining process, and is then subjected to a continuous casting process as molten steel. For example, in the continuous casting process, molten steel is poured into a mold, and a semi-solidified slab in the mold is continuously drawn below the mold, producing semi-finished products (slabs) of various shapes such as slabs, blooms, billets, beam blanks, and the like. The resulting slabs are heated to about 900° C. to 1400° C. in a heating furnace, and rolled into a desired shape by a rolling mill. However, if the molten steel contains copper, there is a risk that the slabs will suffer from hot embrittlement in the heating furnace.

[0012] FIG. 2 is a diagram for explaining hot embrittlement. As illustrated in FIG. 2, by heating a slab 10 in a heating furnace, iron (Fe) is selectively oxidized near the surface of the slab 10 to form iron oxide (Fe t0, t>0) as a component is formed. If a scale has already been formed before the slab is charged into the heating furnace, the scale 11 will be formed in addition to the scale. In this case, the copper component 12 (Cu) contained near the surface of the slab 10 moves to the interface between the slab 10 and the scale 11 and concentrates there. Since the copper component 12 has a low melting point, it becomes liquid in the high-temperature heating furnace and penetrates into the γ grain boundaries in the slab 10. If the slab 10 is hot-rolled in this state, the copper component 12 that has penetrated into the γ grain boundaries may induce cracks 13. The occurrence of cracks 13 in the slab 10 due to the liquid copper component 12 is called hot embrittlement.

[0013] It is known that nickel (Ni) is added to molten steel to suppress this hot embrittlement. By adding nickel to molten steel, the solid solubility limit of copper in the cast slab 10 obtained from the molten steel increases, and the amount of copper diffusing into iron increases, resulting in the formation of a copper-nickel alloy. As shown in FIG. 3, the copper-nickel alloy has a higher melting point than copper metal alone, making it difficult to become liquid. This reduces the amount of liquid phase in the copper alloy, suppressing hot embrittlement.

[0014] However, since nickel is a rare metal and is expensive, it is desirable to reduce the amount of nickel used as much as possible.

[0015] Therefore, it has been considered to lower the nickel concentration inside the molten steel to reduce the amount of nickel used and to increase the nickel concentration on the surface of the steel to increase the solid solubility limit of copper on the surface of the cast slab.

[0016] For example, it is conceivable to sprinkle fine metallic nickel powder on the surface of steel. However, fine metallic powder is difficult to handle because fine metallic powder is flammable and difficult to handle in the atmosphere. Therefore, it is difficult to sprinkle fine metallic nickel powder. Therefore, it is conceivable to sprinkle nickel oxide powder (NiO) on the surface of the steel and increase the nickel concentration on the steel surface through the reduction reaction of nickel oxide. However, sprinkling nickel oxide is also difficult because it is difficult to make it adhere uniformly.

[0017] Therefore, it is conceivable to sprinkle a casting powder containing nickel oxide on the surface of the steel and utilize the substitution reaction of nickel oxide to increase the nickel concentration on the surface of the steel.

[0018] As illustrated in Fig. 4, molten steel 15 is supplied to a mold 50. A casting powder 20 is scattered on the upper surface of the molten steel 15. However, if the viscosity of the casting powder 20 is low, it may not be possible to sufficiently promote the reduction reaction of nickel oxide. For example, there is a risk that the reduction reaction of nickel oxide does not proceed sufficiently because sufficient contact with the steel is not obtained.

[0019] Therefore, in this embodiment, the casting powder 20 having a high viscosity is used to sufficiently promote the reduction reaction of nickel oxide. The casting powder 20 according to this embodiment contains silicon oxide, aluminum oxide, calcium oxide, and nickel oxide, and has a composition ratio in which the sodium oxide content is less than 3 mass% and the fluorine content is less than 5 mass%. By making the sodium oxide content less than 3 mass% and the fluorine content less than 5 mass%, the viscosity of the casting powder 20 can be increased. As a result, when the casting powder 20 is scattered on the surface of molten steel, the reduction reaction of nickel oxide can be sufficiently promoted.

[0020] Hereinafter, the mechanism of suppressing hot embrittlement when the casting powder according to this embodiment is used will be described. As illustrated in Fig. 5, molten steel 15 having scale 16 formed on its surface is obtained in a continuous casting process. In the molten steel 15, a small amount of copper component 12 is dissolved in iron. It is also considered that the copper component 12 is concentrated near the interface between the molten steel 15 and the scale 16 due to selective oxidation of the surface of the molten steel 15.

[0021] Next, the casting powder 20 according to this embodiment is scattered on the molten steel 15. As a result, the casting powder 20 comes into contact with the surface of the scale 16. Under the conditions of the continuous casting process, iron is more easily oxidized than nickel. As a result, reactions such as Fe+NiO→FeO+Ni proceed, the solid solubility limit of copper increases, and the amount of copper diffused into iron increases.

[0022] As a result, the copper component 12 and nickel are alloyed in the scale 16. As a result, a copper-nickel alloy 14 is formed in the scale 16. The copper-nickel alloy 14 has a higher melting point than metallic copper, so it is difficult for the copper-nickel alloy 14 to become liquid even when heated in a heating furnace after being formed into the slab 10. As a result, the copper component is prevented from becoming liquid, and hot embrittlement is suppressed.

[0023] For example, the casting powder 20 preferably has a viscosity of 0.1 Pa·s or more, more preferably has a viscosity of 0.2 Pa·s or more, and further preferably has a viscosity of 0.5 Pa·s or more.

[0024] On the other hand, if the viscosity of the casting powder 20 is too high, the amount of powder that flows into the gap between the mold and the slab may be insufficient, causing the mold and the slab to stick together, which may result in breakout. Therefore, it is preferable to set an upper limit on the viscosity of the casting powder 20. For example, the casting powder 20 preferably has a viscosity of 5.0 Pa·s or less, more preferably has a viscosity of 3.5 Pa·s or less, and even more preferably has a viscosity of 1.5 Pa·s or less.

[0025] If the content of nickel oxide (e.g., NiO) in the casting powder 20 is low, the reduction reaction of nickel oxide may not be sufficiently promoted. Therefore, it is preferable to set a lower limit for the content of nickel oxide in the casting powder 20. For example, the content of nickel oxide in the casting powder 20 is preferably 5.0 mass% or more, more preferably 10.0 mass% or more, and even more preferably 20.0 mass% or more.

[0026] On the other hand, if the content of nickel oxide in the casting powder 20 is high, the melting point may increase. Therefore, it is preferable to set an upper limit on the content of nickel oxide in the casting powder 20. For example, the content of nickel oxide in the casting powder 20 is preferably 50.0 mass% or less, more preferably 40.0 mass% or less, and even more preferably 20.0 mass% or less.

[0027] In addition, since the casting powder 20 has a high viscosity, the reduction reaction of nickel oxide is sufficiently promoted, and therefore it is possible to reduce the content of nickel oxide in the casting powder 20. For example, even if the content of nickel oxide in the casting powder 20 is 5.0 mass% or less, the substitution reaction between iron and nickel can be sufficiently promoted.

[0028] If the content of silicon oxide (e.g., SiO2) in the casting powder 20 is low, the viscosity may decrease. Therefore, it is preferable to set a lower limit for the content of silicon oxide in the casting powder 20. For example, the content of silicon oxide in the casting powder 20 is preferably 20.0 mass% or more, more preferably 25.0 mass% or more, and even more preferably 27.1 mass% or more.

[0029] If the silicon oxide content in the casting powder 20 is high, the viscosity may become too high. Therefore, it is preferable to set an upper limit on the silicon oxide content in the casting powder 20. For example, the silicon oxide content in the casting powder 20 is preferably 60.0 mass% or less, more preferably 50.0 mass% or less, and even more preferably 42.0 mass% or less.

[0030] If the content of aluminum oxide (e.g., Al2O3) in the casting powder 20 is low, the melting point may rise and the lubrication between the mold and the cast piece may be insufficient. Therefore, it is preferable to set a lower limit for the content of aluminum oxide in the casting powder 20. For example, the content of aluminum oxide in the casting powder 20 is preferably 2.9 mass% or more, more preferably 3.0 mass% or more, and even more preferably 5.0 mass% or more.

[0031] If the aluminum oxide content in the casting powder 20 is high, the viscosity may become too high. Therefore, it is preferable to set an upper limit on the aluminum oxide content in the casting powder 20. For example, the aluminum oxide content in the casting powder 20 is preferably 15.0 mass% or less, more preferably 10.0 mass% or less, and even more preferably 7.5 mass% or less.

[0032] If the content of calcium oxide (e.g., CaO) in the casting powder 20 is low, the viscosity may become too high. Therefore, it is preferable to set a lower limit for the content of calcium oxide in the casting powder 20. For example, the content of calcium oxide in the casting powder 20 is preferably 10.0 mass% or more, more preferably 15.0 mass% or more, and even more preferably 20.1 mass% or more.

[0033] If the content of calcium oxide in the casting powder 20 is high, there is a risk of a decrease in viscosity. Therefore, it is preferable to set an upper limit on the content of calcium oxide in the casting powder 20. For example, the content of calcium oxide in the casting powder 20 is preferably 50.0 mass% or less, more preferably 40.0 mass% or less, and further preferably 39.0 mass% or less.

[0034] If the content of magnesium oxide (e.g., MgO) in the casting powder 20 is high, there is a risk of a decrease in viscosity. Therefore, it is preferable to set an upper limit on the content of magnesium oxide in the casting powder 20. For example, the content of magnesium oxide in the casting powder 20 is preferably 10.0 mass% or less, more preferably 5.0 mass% or less, and further preferably 1.9 mass% or less. Note that the casting powder 20 does not necessarily need to contain magnesium oxide (e.g., 0.0 mass%).

[0035] If the content of sodium oxide (e.g., Na2O) in the casting powder 20 is high, there is a risk of increasing the viscosity of the casting powder 20. Therefore, the content of sodium oxide in the casting powder 20 is preferably 5.0 mass% or less, more preferably 3.0 mass% or less, and further preferably 1.1 mass% or less.

[0036] If the fluorine (F) content in the casting powder 20 is high, there is a risk of reducing the viscosity of the casting powder 20. Therefore, the fluorine content in the casting powder 20 is preferably 10.0 mass% or less, more preferably 5.0 mass% or less, and further preferably 2.6 mass% or less.

[0037] If the content of lithium oxide (e.g., Li2O) in the casting powder 20 is high, there is a risk of a decrease in viscosity. Therefore, the content of lithium oxide in the casting powder 20 is preferably 10.0 mass% or less, more preferably 5.0 mass% or less, and further preferably 2.2 mass% or less.

[0038] If the content of boron oxide (e.g., B2O3) in the casting powder 20 is high, the viscosity may be too low. Therefore, it is preferable to set an upper limit on the content of the boron oxide in the casting powder 20. For example, the content of boron oxide in the casting powder 20 is preferably 5.0 mass% or less, more preferably 4.0 mass% or less, and further preferably 2.9 mass% or less.

[0039] In the casting powder 20, if the content ratio (mass %) of calcium oxide / silicon oxide is high, the melting point may rise and lubrication may not be ensured. Therefore, it is preferable to set an upper limit on the content ratio of calcium oxide / silicon oxide in the casting powder 20. For example, in the casting powder 20, the content ratio of calcium oxide / silicon oxide is preferably 1.5 or less, more preferably 1.4 or less, and even more preferably 1.2 or less.

[0040] If the carbon content in the casting powder 20 is high, the melting speed may be slow. Therefore, it is preferable to set an upper limit on the carbon content in the casting powder 20. For example, the carbon content in the casting powder 20 is preferably 20.0 mass% or less, more preferably 15.0 mass% or less, and even more preferably 13.8 mass% or less.

[0041] If the particle size of the casting powder 20 is small, there is a risk of scattering. Therefore, it is preferable to set a lower limit on the particle size of the casting powder 20. For example, the particle size of the casting powder 20 is preferably 50 μm or more, more preferably 200 μm or more, and even more preferably 1000 μm or more.

[0042] On the other hand, if the particle size of the casting powder 20 is large, there is a risk of insufficient melting. Therefore, it is preferable to set an upper limit on the particle size of the casting powder 20. For example, the particle size of the casting powder 20 is preferably 5000 μm or less, more preferably 3000 μm or less, and even more preferably 2000 μm or less.

[0043] If the molten steel 15 contains sufficient nickel, there is a possibility that hot embrittlement can be suppressed even if the casting powder 20 does not contain nickel oxide. FIG. 6 is a diagram showing the relationship between the nickel to copper content ratio Ni / Cu (mass% ratio) in the molten steel 15 and the Cu alloy liquid phase. As shown in FIG. 6, if the Ni / Cu ratio is 0.9 or more, it is found that the Cu alloy liquid phase is hardly generated. Therefore, the casting powder 20 according to this embodiment is preferably applied to the molten steel 15 having a Ni / Cu ratio of less than 0.9, preferably to the molten steel 15 having a Ni / Cu ratio of 0.75 or less, and more preferably to the molten steel 15 having a Ni / Cu ratio of 0.5 or less.

[0044] (Casting method) The casting powder 20 can be used for casting as follows. For example, the casting method according to the present embodiment includes the steps of pouring molten steel 15 having a Ni / Cu ratio of less than 0.9 into a mold 50 as illustrated in Fig. 4, scattering the casting powder 20 on the surface of the molten steel 15, continuously drawing out the cast piece that has solidified in the mold 50 to the lower side of the mold to manufacture cast pieces 10 of various shapes, heating the resulting cast piece 10 at 900°C to 1400°C in a heating furnace, and rolling into a desired shape by a rolling steel mill. According to this casting method, since the casting powder 20 has a sufficient viscosity, the reduction reaction of nickel oxide is sufficiently promoted and hot embrittlement can be suppressed. EXAMPLES

[0045] Hereinafter, an experiment was carried out to confirm the effects of the casting powder 20 according to the above embodiment.

[0046] (Reference example 1) First, Reference Example 1 will be described. In Reference Example 1, an experiment was conducted in a laboratory. A slab 10 having a Cu content of 0.30 mass% and a Ni content of 0.10 mass% was prepared. The slab 10 was heated in a heating furnace and air-cooled to room temperature. When the surface of the slab 10 was checked, it was confirmed that defects such as cracks were present. This is believed to be due to hot embrittlement caused by the low Ni content contained in the slab 10.

[0047] Thereafter, the vicinity of the surface of the slab 10 was observed using a scanning electron microscope (SEM). The top diagram in FIG. 7 is an SEM image of the sample. Next, a composition analysis was performed using an energy dispersive X-ray spectrometer (EDS) for the location indicated by the arrow in the SEM photograph (location within the scale 11). The middle and bottom diagrams in FIG. 7 are diagrams showing the results of the composition analysis. Cu was confirmed at the interface between the scale 11 and the slab 10. Ni was distributed in small amounts. When element mapping was performed near the scale 11, it was confirmed that the location of Cu did not match the location of Ni, and Cu was not alloyed with Ni.

[0048] From the above results, it is believed that in Reference Example 1, when scale 11 was formed, Cu contained near the surface of cast 10 migrated to the vicinity of the interface between cast 10 and scale 11, concentrated there, turned into liquid, and penetrated into the γ grain boundaries within the cast slab.

[0049] (Reference example 2) Next, Reference Example 2 will be described. In Reference Example 2, an experiment was also conducted in a laboratory. A slab 10 having a Cu content of 0.30 mass% and a Ni content of 0.30 mass% was prepared. The slab 10 was heated in a heating furnace and air-cooled to room temperature. When the surface of the slab 10 was checked, it was confirmed that no defects such as cracks had occurred. This is believed to be because hot embrittlement did not occur due to the high Ni content contained in the slab 10.

[0050] Thereafter, the vicinity of the surface of the slab 10 was observed using an SEM. The top diagram in FIG. 8 is an SEM image of the sample. Next, composition analysis was performed by EDS on the location indicated by the arrow (location within the scale 11). The middle and bottom diagrams in FIG. 8 are diagrams showing the results of the composition analysis. Cu was confirmed at the interface between the scale 11 and the slab 10. Ni was distributed in the same manner as Cu. When element mapping was performed near the scale 11, multiple locations were confirmed where the location of Cu coincided with the location of Ni. From these results, it is considered that Cu was alloyed with Ni to form a Cu-Ni alloy.

[0051] From the results of Reference Examples 1 and 2, it was confirmed that hot embrittlement was suppressed by the formation of a copper-nickel alloy near the surface of the slab 10. Based on the above results, the following experiment was carried out.

[0052] (Examples 1 to 10 and Comparative Examples 1 to 4) In Examples 1 to 10 and Comparative Examples 1 to 4, in order to simulate the scattering of casting powder on molten steel, a slab 10 of metallic Fe was placed in an alumina crucible 30 as shown in Fig. 9(a). Casting powder 20 was scattered on the slab 10 to prepare a sample. The slab 10 had a cubic shape of 10 mm x 10 mm x 10 mm as shown in Fig. 9(b).

[0053] The Cu content in the slab 10 was 0.30 mass% in all of Examples 1 to 10 and Comparative Examples 1 to 4. The Ni content in the slab 10 was 0.10 mass% in Examples 1 to 6, 8 to 10 and Comparative Examples 1 and 2, and 0.30 mass% in Example 7 and Comparative Examples 3 and 4.

[0054] In Comparative Examples 2 and 4, casting powder No. 1 was used. In Examples 1, 5 and 7, casting powder No. 2 was used. In Examples 2 and 6, casting powder No. 2 was used. In Examples 3 and 9, casting powder No. 4 was used. In Example 4, casting powder No. 5 was used. In Examples 8 and 10, casting powder No. 10 was used. In Comparative Examples 1 and 3, no casting powder was sprayed.

[0055] Next, the inside of the heating furnace 40 was heated as shown in Fig. 10. The atmosphere inside the heating furnace 40 was air. In Examples 1 to 4, 7, and 8 and Comparative Examples 1 to 4, the temperature inside the heating furnace 40 was set to 1150°C. In Examples 5, 6, 9, and 10, the temperature inside the heating furnace 40 was set to 1400°C.

[0056] Next, the samples were placed in the heating furnace 40 and held therein for a predetermined time. The holding time was 30 minutes in Examples 1, 2, 5, 7, and 9 and Comparative Examples 2 and 4. The holding time was 10 minutes in Examples 3, 4, 6, 8, and 10 and Comparative Examples 1 and 3. Thereafter, the samples were removed from the heating furnace 40 and air-cooled to room temperature.

[0057] The conditions for Examples 1 to 10 and Comparative Examples 1 to 4 are shown in Table 1. [Table 1]

[0058] The compositions of the casting powders No. 1 to No. 6 are shown in Table 2. In the casting powder No. 1, the NiO content was 0.0 mass%, the SiO2 content was 42.0 mass%, the Al2O3 content was 7.5 mass%, the CaO content was 25.1 mass%, the MgO content was 1.9 mass%, the Na2O content was 0.1 mass%, the F content was 0.0 mass%, the Li2O content was 2.2 mass%, the B2O3 content was 2.9 mass%, the carbon content was 13.8 mass%, and the CaO / SiO2 mass% ratio was 0.6.

[0059] In the casting powder No. 2, the NiO content was 5.0 mass%, the SiO2 content was 39.9 mass%, the Al2O3 content was 7.1 mass%, the CaO content was 23.8 mass%, the MgO content was 1.8 mass%, the Na2O content was 0.1 mass%, the F content was 0.0 mass%, the Li2O content was 2.1 mass%, the B2O3 content was 2.8 mass%, the carbon content was 13.1 mass%, and the CaO / SiO2 mass% ratio was 0.6.

[0060] In the casting powder No. 3, the NiO content was 20.0 mass%, the SiO2 content was 33.6 mass%, the Al2O3 content was 6.0 mass%, the CaO content was 20.1 mass%, the MgO content was 1.5 mass%, the Na2O content was 0.1 mass%, the F content was 0.0 mass%, the Li2O content was 1.8 mass%, the B2O3 content was 2.3 mass%, the carbon content was 11.0 mass%, and the CaO / SiO2 mass% ratio was 0.6.

[0061] In the casting powder No. 4, the NiO content was 20.0 mass%, the SiO2 content was 27.1 mass%, the Al2O3 content was 5.6 mass%, the CaO content was 32.9 mass%, no MgO was added, no Na2O was added, the F content was 2.2 mass%, no Li2O was added, no B2O3 was added, the carbon content was 7.8 mass%, and the CaO / SiO2 mass% ratio was 1.2.

[0062] In the casting powder No. 5, the NiO content was 20.0 mass%, the SiO2 content was 33.1 mass%, the Al2O3 content was 2.9 mass%, the CaO content was 22.0 mass%, no MgO was added, the Na2O content was 1.1 mass%, the F content was 1.4 mass%, the Li2O content was 1.1 mass%, the B2O3 content was 2.7 mass%, the carbon content was 6.9 mass%, and the CaO / SiO2 mass% ratio was 0.7.

[0063] In the casting powder No. 6, the NiO content was 5.0 mass%, the SiO2 content was 32.2 mass%, the Al2O3 content was 6.7 mass%, the CaO content was 39.0 mass%, no MgO was added, no Na2O was added, the F content was 2.6 mass%, no Li2O was added, no B2O3 was added, the carbon content was 9.2 mass%, and the mass% ratio of CaO / SiO2 was 1.2. [Table 2]

[0064] Thereafter, the vicinity of the interface between the casting powder 20 and the slab 10 was observed using an SEM for the samples of Examples 1 to 10 and Comparative Examples 2 and 4. It was confirmed that the casting powder 20 was in close contact with the slab 10 in all of Examples 1 to 10 and Comparative Examples 2 and 4. This is believed to be because high viscosity was obtained because the sodium oxide content in the casting powder was less than 3 mass% and the fluorine content was less than 5 mass%.

[0065] The top diagram of FIG. 11 is an SEM image of the sample of Example 1. Something like a Cu alloy was confirmed in the scale 11. Next, a composition analysis was performed by EDS (energy dispersive X-ray spectroscope) on the part indicated by the arrow (part in the scale 11). The middle and bottom diagrams of FIG. 11 are diagrams showing the results of the composition analysis. Cu and Ni were confirmed in the scale 11. 2.72 mass% of Ni and 1.40 mass% of Cu were confirmed. In addition, when element mapping was confirmed, multiple parts were confirmed where the position of Cu and the position of Ni coincided. From these results, it is considered that Cu was alloyed with Ni to form a Cu-Ni alloy.

[0066] Infiltration of Cu into the slab 10 was not observed. This is believed to be because Cu contained in the slab 10 was alloyed with Ni, increasing the melting point and suppressing liquid phase formation.

[0067] When the SEM photographs of Examples 2 to 10 were examined, multiple locations were confirmed where the positions of Cu and Ni were aligned, similar to Example 1. From these results, it is considered that Cu was alloyed with Ni to form a Cu-Ni alloy, similar to Reference Example 2. From the above, it is considered that hot embrittlement is suppressed in Examples 1 to 10, similar to Reference Example 2.

[0068] The top diagram in FIG. 12 is an SEM image of the sample of Comparative Example 2. The portion indicated by the arrow (the portion in the slab 10) was subjected to composition analysis by EDS. The middle and bottom diagrams in FIG. 12 are diagrams showing the results of the composition analysis. Cu was confirmed in the slab 10. 6.16 mass% of Cu was confirmed, but Ni was not confirmed. From these results, it is considered that the portion is a portion in which Cu has infiltrated into the slab 10. Therefore, it is considered that hot embrittlement occurs in Comparative Example 2, as in Reference Example 1. In Comparative Example 1, as in Comparative Example 2, a portion in which Cu is thought to have infiltrated into the slab was confirmed.

[0069] (Example 11 and Comparative Example 5) In Example 11 and Comparative Example 5, experiments were carried out on the same day using an actual continuous casting machine. In Example 11, in the actual continuous casting machine, casting powder 20 was scattered on molten steel 15 poured into a mold 50 to semi-solidify it, and a cast 10 was obtained. The obtained cast 10 was heated in a heating furnace and air-cooled to room temperature. In Example 11, casting powder No. 6 was used. In Comparative Example 5, casting powder not containing nickel oxide was used. In Example 11, 41 cast pieces were produced, and in Comparative Example 5, 27,174 cast pieces were produced. The surface of each cast piece was visually checked for defects. The results are shown in FIG. 13(a). As shown in FIG. 13(a), the percentage of cast pieces with defects was 0.4% in Comparative Example 5, while the percentage of cast pieces with defects was 0% in Example 11.

[0070] The top diagram of FIG. 14 is an SEM image of the sample of Example 11. Something like a Cu alloy was confirmed in the scale 11. Next, a composition analysis was performed by EDS (energy dispersive X-ray spectroscope) on the part indicated by the arrow (part in the scale 11). The middle and bottom diagrams of FIG. 14 are diagrams showing the results of the composition analysis. Cu and Ni were confirmed in the scale 11. 5.15 mass% Ni and 4.22 mass% Cu were confirmed. In addition, when element mapping was confirmed, multiple parts were confirmed where the position of Cu and the position of Ni coincided. From these results, it is considered that Cu was alloyed with Ni to form a Cu-Ni alloy.

[0071] (Example 12 and Comparative Example 6) In Example 12 and Comparative Example 6, experiments were carried out on the same day using an actual continuous casting machine. In Example 12, in the actual continuous casting machine, casting powder 20 was scattered on molten steel 15 poured into a mold 50 to semi-solidify it, and a slab 10 was obtained. The obtained slab 10 was heated in a heating furnace and air-cooled to room temperature. In Example 12, casting powder No. 2 was used. In Comparative Example 6, casting powder not containing nickel oxide was used. In Example 12, 55 slabs were produced, and in Comparative Example 5, 6571 slabs were produced. The surface of each slab was visually checked for defects. The results are shown in FIG. 13(b). As shown in FIG. 13(b), the percentage of slabs with defects was 4.5% in Comparative Example 6, while the percentage of slabs with defects was 1.8% in Example 12.

[0072] The top diagram of FIG. 15 is an SEM image of the sample of Example 12. Something like a Cu alloy was confirmed in the scale 11. Next, a composition analysis was performed by EDS (energy dispersive X-ray spectroscope) on the part indicated by the arrow (part in the scale 11). The middle and bottom diagrams of FIG. 15 are diagrams showing the results of the composition analysis. Cu and Ni were confirmed in the scale 11. 4.21 mass% of Ni was confirmed, and 4.17 mass% of Cu was confirmed. In addition, when element mapping was confirmed, multiple parts were confirmed where the position of Cu and the position of Ni coincided. From these results, it is considered that Cu was alloyed with Ni to form a Cu-Ni alloy.

[0073] Although the embodiments of the present invention have been described in detail above, the present invention is not limited to such specific embodiments, and various modifications and variations are possible within the scope of the gist of the present invention described in the claims. [Explanation of symbols]

[0074] 10 Casting 11. Scale 12 Copper Content 13. Crack 14 Copper-nickel alloy 15 Molten Steel 16 Scale 20 Casting Powder 30 Alumina crucible 40 Furnace 50 Mold

Claims

1. A casting powder comprising silicon oxide, aluminum oxide, calcium oxide, and nickel oxide, the powder having a sodium oxide content of less than 3 mass% and a fluorine content of less than 5 mass%.

2. 2. The casting powder according to claim 1, wherein the content of the nickel oxide is 20.0 mass % or less.

3. 2. The casting powder according to claim 1, wherein the content of said silicon oxide is 27.1 mass % or more and 42.0 mass % or less.

4. 2. The casting powder according to claim 1, wherein the content of said aluminum oxide is 2.9 mass % or more and 7.5 mass % or less.

5. 2. The casting powder according to claim 1, wherein the calcium oxide content is 20.1 mass % or more and 39.0 mass % or less.

6. 2. The casting powder according to claim 1, wherein the magnesium oxide content is 0.0 mass % or more and 1.9 mass % or less.

7. 2. The casting powder according to claim 1, wherein the content of said sodium oxide is 1.1 mass % or less.

8. 2. The casting powder according to claim 1, wherein the fluorine content is 2.6 mass % or less.

9. 2. The casting powder according to claim 1, wherein the content of lithium oxide is 2.2 mass % or less.

10. 2. The casting powder according to claim 1, wherein the content of boron oxide is 2.9 mass % or less.

11. 2. The casting powder according to claim 1, wherein a content ratio of said calcium oxide to said silicon oxide is 1.2 or less.

12. 2. The casting powder according to claim 1, wherein the carbon content is 13.8 mass % or less.

13. pouring molten steel having a Ni / Cu ratio of less than 0.9 into a mold and scattering the casting powder according to claim 1 on a surface of the molten steel; and semi-solidifying the molten steel in the mold to obtain a cast piece.

Citation Information

Patent Citations

  • Medium and low carbon steel continuous casting mold powder as well as preparation method thereof and continuous casting method

    CN102218514A

  • Particulate slagging composition for extended optimum continuous casting of steel

    JP1980154520A

  • Mold powder for continuous casting of steel

    JP1996052550A

  • Powder for continuous casting and continuous casting method using this powder

    JP2003266158A

  • Continuous casting method

    JP2006239716A